Improvisação livre e forma: processo criativo entre estímulos e efeitos - Ciacchi, Matteo (2019)
“Free improvisation” is one of the names given to a broad musical movement developed and established in the 1960s, in which the concept of improvisation plays a central role in performance practice. Free improvisation is commonly defined as a music in which previously determined structures, conventions or stylistic traits are kept at a minimum, or totally absent ideally. Defined in this way, free improvisation offers a methodological challenge for a scientific approach, which the present work tries to address: how the creative process of a free improviser works? In other words: how can the concept of “free”, “total” or “pure” improvisation serve as stimulus or productive principle for the construction of a performance? We begin by a historiographical inquiry on the use of the term “improvisation” up until the development of this practice, trying to understand what concepts were attached to the word and how they have been translated musically. We then proceed to understand the concept of musical form in a broader way, so that it could be used to understand a music that dismisses the notion of preconceived structure, and assess the usefulness of this concept for a critical analysis of free improvisation. The work concludes with the analysis of a performance we considered canonical of free improvisation, trying to apply the concepts and analytic ideas developed along the research.